Prehistoric fires and the shaping of colonial transported landscapes in southern California: A paleoenvironmental study at Dune Pond, Santa Barbara County. (15th March 2015) - Ejarque, Ana; Anderson, R. Scott; Simms, Alexander R.; Gentry, Beau J.
Abstract: Using a novel combination of paleoecologic proxies including pollen, non-pollen palynomorphs (NPPs), macroscopic charcoal, and Spheroidal Carbonaceous Particles (SCPs), 5000 years of landscape change, fire history and land-use have been reconstructed from Dune Pond, Santa Barbara County, California. The pond was sensitive to Holocene regional climatic variability, showing different phases of lower (4600–3700 cal yr BP, 2100–700 cal yr BP, historical period) and higher (3700–2100 cal yr BP, 700–150 cal yr BP) local moisture availability. During this period the landscape was dominated by a coastal mosaic vegetation including dune mats, coastal scrub and salt marshes on the dunes and backdunes, with chaparral and oak woodland growing in the valley plains and foothills. Fire was intimately linked with such dominating mosaic vegetation, and the combination of wet conditions and the presence of nearby human settlement were a trigger favoring coastal fires for at least two periods: from 3100 to 1500 cal yr BP and from 650 cal yr BP until the 18th century. In both cases fire was an important tool to keep an open coastal landscape attractive to hunting wildlife. Finally, matching this varied range of high-resolution paleoecological proxies with historical records we could characterize the development of colonial transported landscapes following the Euro-American settlement of Santa Barbara. The introduction of livestock grazing by Spanish colonists favored erosive processes and the introduction of fecal-borne parasites in freshwater bodies, negatively impacted salt and brackish coastal marshes, and promoted the invasion of alien grasses and ruderals. This agro-pastoral landscape was consolidated during the American period, with a greater role for cultivation, the development of industrial activities and increased population. Despite negative environmental consequences such as the loss of native habitats, exotic land-uses and plants introduced during the historical period significantly contributed to the configuration of a cultural landscape which forms part of the cultural heritage of California. Highlights: We reconstruct 5000-yr of landscape change, fire history and land-use in S California. Increased human settlement and wet conditions triggered late Holocene coastal fires. The development of Euro-American transported landscapes was characterized. Colonial grazing favored Baccharis scrub and alien grasses over native coastal marshes. Spheroidal Carbonaceous Particles allowed dating the industrial period.